If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + -8x = -10 + -2x + -7x Combine like terms: -2x + -7x = -9x -3 + -8x = -10 + -9x Solving -3 + -8x = -10 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. -3 + -8x + 9x = -10 + -9x + 9x Combine like terms: -8x + 9x = 1x -3 + 1x = -10 + -9x + 9x Combine like terms: -9x + 9x = 0 -3 + 1x = -10 + 0 -3 + 1x = -10 Add '3' to each side of the equation. -3 + 3 + 1x = -10 + 3 Combine like terms: -3 + 3 = 0 0 + 1x = -10 + 3 1x = -10 + 3 Combine like terms: -10 + 3 = -7 1x = -7 Divide each side by '1'. x = -7 Simplifying x = -7
| 2x-5(x-4)=-3+4x-12 | | -6b-8=19 | | 4g-6-9=3 | | 3=5-2a | | 8x-1=8(x-3) | | 5x+8(-4x-9)=-10(-2x-9)+26 | | x^2-6x-96=0 | | 2k-1=-5+3k | | 24x=24+7x | | -3(4p+4)-2(6-14p)-3(7+5p)=0 | | 2(-5U+10)+2u= | | 2-5a=-8 | | 7x+5x-38=95-7x | | 2k-1=-5+2k | | 5b-13=3b+1 | | t=6s+18.01 | | 5z+30=40 | | 5-3p+9=13p+8 | | 3f+2=5 | | 5-4p=11 | | (5x-1)(x-5)=0 | | 0=324+2*3.65*x | | 9-(x+6)=9x-7 | | 0.3x-2.9=4.7x+2.6 | | 9x^4-25x^3+16x^2=0 | | 4n+5n=27 | | -2x^2+17x-35=0 | | (10x-10)=(8x+14) | | -8+3r=-3+2r | | 6+x+6+x=6x | | -8x+11+9x=2+x+9 | | 10r=4r+12 |